Evidence of enhanced photocurrent response in corannulene films. Issue 72 (25th September 2017) - Pastukhova, N.; Samos, L. Martin; Zoppi, L.; Pavlica, E.; Mathew, J.; Bratina, G.; Siegel, J. S.; Baldridge, K. K.
Abstract : Experimental optical absorption and photoconductivity spectra of thin films with GW–BSE theoretical predictions provide evidence for diffuse super atomic molecular orbitals (SAMOs) in corannulene, C20 H10 . Abstract : Photoconductivity spectra measured in non-crystalline corannulene thin layers are compared to optical absorption in solution phase and thin films. The unexpected enhanced photoconductivity is correlated with GW–BSE theoretical predictions of corannulene gas-phase excitonic spectra. Theoretical analysis reveals a consistent contribution involving transitions to Super Atomic Molecular Orbitals (SAMOs), a unique set of diffuse orbitals typical of curved conjugated constructs. Results suggest SAMO population via direct photoexcitation as a potential mechanism towards exploiting these diffuse orbitals as conducting channels in suitably assembled quantum nanostructures or solids.